Pengaruh Karakter, Pola Asuh dan Masalah Orangtua Terhadap Perilaku Anak Di Sekolah - Dewi, Chandra (STAI Serdang Lubuk Pakam, 2019)
Discussing about children, is an interesting discussion for parents and educators because behind it all there are unique facts relating to children's behavior and their correlation with children's problems. What happens at home or at school. Families, especially mothers are the first madrasas children before studying in formal and non-formal educational institutions, so the family must have a greater role in terms of being responsible for educating children. The role of parents must be able to meet the psychological and physical needs of a child so that the child as the holder of the line can be a person that his parents can be proud of. Good interaction between parents and children can create a conducive relationship and will greatly affect children's development in terms of cognitive and emotional. The problem is, has this matter become an important priority for parents? This is where the author feels the need to do research because many see the fact that it happens precisely the attitudes and behavior of parents become a problem trigger for children in behaving in their social environment, especially the school environment. The author would like to see how much